'Simply in virtue of being human'? A critical appraisal of a human rights commonplace. (2nd September 2018) - Fasel, Raffael N
ABSTRACT: It has become a commonplace that human beings possess human rights 'simply in virtue of being human'. Exactly what this formula entails and whether it is cogent remains largely obscure, however. To remedy this situation, the article distinguishes between an interpretation of the formula according to which 'being human' is a practical condition for holding human rights and a reading which takes 'being human' to be a moral reason for holding human rights. It argues that only under the second reading is there a limited sense in which it is correct that human beings possess human rights 'simply in virtue of being human'. The article also considers if the concept of human dignity can provide a more convincing approach to the formula, and argues that it cannot.